Biological Behavior of Bioactive Glasses SinGlass (45S5) and SinGlass High (F18) in the Repair of Critical Bone Defects - Dayane Maria Braz Nogueira; Marcelie Priscila de Oliveira Rosso; Paulo Sérgio da Silva Santos; Manoel Damião Sousa-Neto; Alice Corrêa Silva-Sousa; Cleverson Teixeira Soares; Carlos Henrique Bertoni Reis; Jéssica de Oliveira Rossi; Cleuber Rodrigo de Souza Bueno; Daniela Vieira Buchaim; Rogério Leone Buchaim; Mariana Schutzer Ragghianti Zangrando (Biomolecules)
This study evaluated the osteogenic potential of the bioactive glasses SinGlass (45S5) and SinGlass High (F18) in regenerating critical bone defects in rat calvaria. Both biomaterials promoted new bone formation around the particles, with the SinGlass High (F18) group exhibiting a higher rate of bone maturation. Histomorphological and birefringence analyses revealed better organization of the newly formed bone in the biomaterial-treated groups, and immunohistochemistry indicated the expression of osteogenic markers such as osteocalcin, immunostaining for bone morphogenetic protein 2 (BMP 2), and immunostaining for bone morphogenetic protein 4 (BMP 4). Microtomography computadorized (Micro-CT) revealed centripetal bone formation in both groups, with greater integration of the particles into the surrounding bone tissue. The superior performance of SinGlass High (F18) was attributed to its higher potassium and magnesium content, which enhance osteoconductivity. After 42 days, the SinGlass High (F18) group showed the highest percentage of new bone formation, in line with previous studies. Although our results are promising, the limited follow-up period and use of a single animal model highlight the need for further research to validate clinical applicability. SinGlass High (F18) appears to be a viable alternative to autografts in bone repair, with potential to improve tissue integration and accelerate recovery.